Operations management - Stevenson, William J. (New York : McGraw-Hill Education, 2015)
"Stevenson's Operations Management features integrated, up-to-date coverage of current topics and industry trends, while preserving the core concepts that have made the text the market leader in this course for over a decade. Stevenson's careful explanations and approachable format support students in understanding the important operations management concepts as well as applying tools and methods with an emphasis on problem solving. Through detailed examples and solved problems, short cases and readings on current issues facing businesses, and auto-gradable end of chapter problems and application-oriented assignments available in Connect Operations Management, students learn by doing, and the Twelfth Edition continues to offer more support for 'doing Operations' than any other"--
Machine generated contents note: 1. Introduction to Operations Management2. Competitiveness, Strategy, and Productivity3. Forecasting4. Product and Service DesignSupplement: Reliability5. Strategic Capacity Planning for Products and ServicesSupplement: Decision Theory6. Process Selection and Facilities Layout7. Work Design and MeasurementSupplement: Learning Curves8. Location Planning and AnalysisSupplement: The Transportation Model9. Management of Quality10. Quality ControlSupplement: Acceptance Sampling11. Aggregate Planning and Master Scheduling12. MRP and ERP13. Inventory Management14. JIT and Lean OperationsSupplement: Maintenance15. Supply Chain Management16. Scheduling17. Project Management18. Management of Waiting Lines19. Linear ProgrammingAppendix A Answers to Selected ProblemsAppendix B TablesAppendix C Working with the Normal DistributionCompany IndexSubject Index.
Includes bibliographical references and index.
AAL
Keywords: Production management; BUSINESS & ECONOMICS / Operations Research